2002
DOI: 10.1074/jbc.m202568200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Calcium-independent Phospholipase A2 (iPLA2) β, and Not iPLA2γ, as the Mediator of Arginine Vasopressin-induced Arachidonic Acid Release in A-10 Smooth Muscle Cells

Abstract: The agonist-stimulated release of arachidonic acid (AA) from cellular phospholipids in many cell types (e.g. myocytes, ␤-cells, and neurons) has been demonstrated to be primarily mediated by calcium-independent phospholipases A 2 (iPLA 2 s) that are inhibited by the mechanism-based inhibitor (E)-6-(bromomethylene)-3-(1-naphthalenyl)-2H-tetrahydropyran-2-one (BEL). Recently, the family of mammalian iPLA 2 s has been extended to include iPLA 2 ␥, which previously could not be pharmacologically distinguished from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
187
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(201 citation statements)
references
References 58 publications
9
187
1
4
Order By: Relevance
“…The majority of immunoreactive protein for both isoforms was detected in the cytosol (Figure 4). A recent manuscript has described the selective inhibition of iPLA 2 β and iPLA 2 γ using the S-and R-enantiomers of BEL respectively [19]. We incubated the cytosolic fraction from human platelets with increasing concentrations of (R)-BEL, (S)-BEL or racemic BEL for 10 minutes prior to assay of iPLA 2 activity ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of immunoreactive protein for both isoforms was detected in the cytosol (Figure 4). A recent manuscript has described the selective inhibition of iPLA 2 β and iPLA 2 γ using the S-and R-enantiomers of BEL respectively [19]. We incubated the cytosolic fraction from human platelets with increasing concentrations of (R)-BEL, (S)-BEL or racemic BEL for 10 minutes prior to assay of iPLA 2 activity ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…This isoform has recently been identified and characterized [7] and has been found to be uniquely sensitive to (R)-BEL [19]. Human iPLA 2 -γ has multiple alternative start sites for translation resulting in functional PLA 2 γ proteins with MW of 63-, 74-, 77-and 88-kDa [7].…”
Section: Discussionmentioning
confidence: 99%
“…For iPLA 2 ␤, several important signaling functions have been suggested, including its role in agonist-induced stimulation of smooth muscle (20) and endothelial cells (21), in lymphocyte proliferation (22), and in endothelium-dependent vascular relaxation (21). Very recently, it was reported that myocardial ischemia activates iPLA 2 ␤ in intact myocardium, and that iPLA 2 ␤ activation is sufficient to induce malignant ventricular arrhythmias (23).…”
Section: Discussionmentioning
confidence: 99%
“…iPLA 2 has been shown to be implicated in many cellular functions ranging from basal fatty acid reacylation reactions (17), to playing major roles in intracellular signaling cascades, including its involvement in agonist-induced eicosanoid production (18,19), stimulation of smooth muscle (20) and endothelial cells (21), in lymphocyte proliferation (22), and in endothelium-dependent vascular relaxation (21). Very recently, it has been reported that myocardial ischemia activates iPLA 2 ␤ in intact myocardium, and that this iPLA 2 ␤ activation is sufficient to induce malignant ventricular arrhythmias (23), and also that functional iPLA 2 is required for activation of store-operated channels and capacitative Ca 2ϩ influx in several cell types (24).…”
mentioning
confidence: 99%
“…Cytosolic iPLA 2 (Group VIA-1 and VIA-2 PLA 2 ) are suggested to me-diate ischemia-induced myocardial dysfunction (13), cAMP release in rat mesangial cells (14), arginine vasopressin-induced arachidonic acid release in A-10 smooth muscle cells (15), and nuclear phospholipid mass decreases after myocardial ischemia (16). However, the exact mechanisms controlling cytosolic iPLA 2 , such as Group VIA-1 and VIA-2 PLA 2 , in these processes and the exact phospholipids involved are not known.…”
mentioning
confidence: 99%